Techno-Economic Analysis Of Hydrogen Storage Technologies For Transport Applications - Fachri Munadi; Dijan Supramono (Jurnal Informasi, Sains dan Teknologi, 2024)
he world's energy industries contribute 87% to the increase in global greenhouse gases. To reduce global greenhouse gas emissions, hydrogen as clean energy is an alternative energy source with a gravimetric energy density of 120 MJ/kg and a volumetric density of 0.0824 kg/m3. The main challenge of hydrogen as an energy carrier is its low volumetric density, thus requiring hydrogen storage technology at higher volumetric densities. Hydrogen storage systems are crucial to the hydrogen supply chain process, especially in terms of its economics. The hydrogen storage system consists of hydrogenation, transportation, and dehydrogenation processes. This paper uses the techno-economic analysis of five types of hydrogen storage technologies: compressed hydrogen, liquid Hydrogen, liquid organic hydrogen carrier, metal hydride, and ammonia. Hysys was introduced to help process design, process modeling, and equipment sizing of each technology. System costs ($/kg) are determined based on projected Capital Expenditure (CapEx) and Operational expenditure (OpEx) of each hydrogenation and dehydrogenation process, as well as shipping transportation cost at 2000 km. The results show that liquid organic hydrogen carrier had the lowest system cost of $2.84/kg, followed by metal hydride at $2.95/kg, compressed hydrogen at $3.33/kg, ammonia at $7.21/kg, and liquid hydrogen at $11.51/kg. However, the storage efficiency of liquid organic hydrogen carriers is only 8.73%, compared to compressed hydrogen at 99%. The results show that the cost of hydrogen storage systems needs to be significantly reduced for long-term and large-scale applications.